(untitled) (International Journal of Pathology, 2021)
Disclaimer: Following article is not an original research article, rather it is a compilation of information taken from different sources particularly Wikipedia, 1001 Inventions, 3rd Edition published by National Geographic and famousscientists.org; We acknowledge and thank them for this very valuable information for our esteemed readers. Please note that IJP is a non-profit research journal … editors When the Dark Ages had engulfed the West, there was just the opposite situation in the other part of the world. In the vastly expanded Muslim ruled world there was glittering Golden Age. The light of knowledge was illuminating all aspects and all spheres of human life i.e., Education, Governance, Justice, Civilization, Human rights, Science and Health etc. Interestingly and rather miraculously this Golden Age emanated from an area which was considered the most backward i.e., Arabian Peninsula. That was literally a Big Bang in all these fields. The epicenter for this remarkable and the most fascinating phenomenon was Makkah and Madinah (Now in Saudi Arabia); The rays of the light not only illuminated Islamic World but also gradually penetrated deep into Europe steadily removing the darkness and paving the path for renaissance and industrial revolution. This Golden Glittering era produced numerous giants among men in all aforementioned fields. These men and women were the most upright and clear-headed individuals with golden heart and brightest vision. Among these was Ibn e Sina born about 1100 years ago in Uzbekistan and died at age of 57 in Hamadan. He is also known as prince of medicine and father of modern medicine. It was a common proverb in Europe at that time and afterwards that if you want to be a physician you should be Avicennian referring to his corrupted Latin name..